2013
DOI: 10.1167/iovs.12-10709
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four–Hour Pattern of Intraocular Pressure in Untreated Patients with Ocular Hypertension

Abstract: PURPOSE.To characterize the 24-hour pattern of intraocular pressure (IOP) in untreated ocular hypertensive (OHTN) patients.METHODS. IOP measurements were taken every 2 hours during a 24-hour period from 15 untreated OHTN patients (ages 41-77 years). Measurements were both sitting and supine (diurnal) and supine only (nocturnal). Mean diurnal and nocturnal IOPs in the OHTN group were compared to previously reported values in age-matched healthy and glaucomatous eyes. Post hoc analysis compared the 24-hour IOP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 20 publications
4
46
0
1
Order By: Relevance
“…The mean sitting IOP in these patients was 22.9±1.5 and 22.3±0.7 mm Hg, respectively. In a study on patients with untreated OHT, Grippo et al 17 reported that baseline 24 h IOP pattern in patients with OHT was similar to that in glaucomatous patients. In contrast to non-converters, patients with OHT who converted to glaucoma were found to be significantly different from healthy controls.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The mean sitting IOP in these patients was 22.9±1.5 and 22.3±0.7 mm Hg, respectively. In a study on patients with untreated OHT, Grippo et al 17 reported that baseline 24 h IOP pattern in patients with OHT was similar to that in glaucomatous patients. In contrast to non-converters, patients with OHT who converted to glaucoma were found to be significantly different from healthy controls.…”
Section: Discussionmentioning
confidence: 89%
“…Some papers on DV of IOP have taken IOP measurements in the sitting position during the day and supine position at night 17. This may confound their findings and what was attributed to DV alone may also have a postural variation component to it, which may have gone unrecognised.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study also showed that IOP fluctuation is significantly higher in eyes with primary chronic ACG (7.69±3.03 mm Hg) or POAG (8.31±2.58 mm Hg) compared to normal eyes (4.83±2.46 mm Hg) 38. Similarly, Grippo et al 39 followed the protocol of prior works and combined results to determine that daytime IOP variation—though not nighttime variation—was significantly greater in subjects with OHT and glaucoma than healthy individuals.…”
Section: Short-term Iop Fluctuationmentioning
confidence: 89%
“…There was no association between peak IOP or IOP fluctuation (defined as the difference between peak and minimum IOP during a 24-h period) and cross-sectional measurements of glaucoma severity including SAP MD. A small study examining 24-h IOP in patients with ocular hypertension also found no evidence of IOP fluctuation as a risk factor for developing glaucoma [22] . In contrast, De Moraes et al [17] recently reported that certain characteristics of the 24-h IOP profile, measured using the CLS, may be useful markers of faster rates of disease progression.…”
Section: Discussionmentioning
confidence: 97%